2004
DOI: 10.1080/0261976042000223015
|View full text |Cite
|
Sign up to set email alerts
|

Specific mentoring: a theory and model for developing primary science teaching practices

Abstract: The transition from generic mentoring to specific mentoring practices can provide a stronger focus for developing preservice primary teachers (mentees) in subject-specific areas. Constructivist theory and a five-factor model towards specific subject mentoring are proposed as ways to develop mentees' teaching practices. Firstly, constructivist theory complements mentoring within field experiences (practicum/internship), as it can be used to build upon prior understandings towards developing the mentee's knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 9 publications
6
101
0
14
Order By: Relevance
“…The "Mentoring for Effective Mathematics Teaching" (MEMT) survey instrument evolved through a series of preliminary investigations on Mentoring for Effective Primary Science Teaching (MEPST; Hudson, 2003;Hudson, 2004aHudson, , 2004bHudson et al, 2005;Hudson, 2007), which also identified the link between the generic mentoring literature and the items on the survey instrument. The MEMT survey instrument was designed to gather data about preservice teachers' perceptions of their mentoring for teaching primary mathematics (Hudson, 2009).…”
Section: Data Collection Methods and Analysismentioning
confidence: 99%
“…The "Mentoring for Effective Mathematics Teaching" (MEMT) survey instrument evolved through a series of preliminary investigations on Mentoring for Effective Primary Science Teaching (MEPST; Hudson, 2003;Hudson, 2004aHudson, , 2004bHudson et al, 2005;Hudson, 2007), which also identified the link between the generic mentoring literature and the items on the survey instrument. The MEMT survey instrument was designed to gather data about preservice teachers' perceptions of their mentoring for teaching primary mathematics (Hudson, 2009).…”
Section: Data Collection Methods and Analysismentioning
confidence: 99%
“…Because mentoring practices in teacher education are based on a variety of contexts including prospective, in-service, or distance teacher education, the expectations and roles are not clearly and systematically conceptualized by the national councils of education (Hudson, 2004;Koç, 2012). Due to its context-dependent nature, it is difficult to set and determine a specific definition of the mentoring roles and practices (Lai, 2005(Lai, , 2010.…”
Section: The Role Of Mentoring In Practice Teachingmentioning
confidence: 99%
“…We do not know, however, whether those same positive trends are true for physical educators. Hudson (2004) suggests that mentoring is subject matter specific, so we cannot assume that what works in general education can be directly transferred to physical education. This investigation contributes to that knowledge base as well as serving as a starting point for future research.…”
Section: Final Thoughts and Future Directionsmentioning
confidence: 99%